Evaluation of double-stage Anaerobic Fluidized Bed Reactor (AFBR) for digestion of leachate: correlation of kinetic parameter with operational condition and process - Prastyo, Elli; Budhijanto, Wiratni; Sudibyo, Hanifrahmawan (Universitas Mercu Buana, 2025)
The objective of this study is to investigate the performance of using an advanced fluidized bed reactor (AFBR) of a double column configuration in breaking down leachate into biogas. The relationship of the kinetic parameters with the operating conditions and the performance of the double-column reactor during anaerobic digestion was examined. The substrate concentration, microorganism population, hydraulic retention time value, growth rate, and death rate of microorganisms were employed as reference points for evaluating anaerobic digestion performance and assessing the operating conditions. The results demonstrated that there was no notable correlation between the formation of volatile fatty acids (VFA) in the acidogenic reactor (R1), the degradation of VFA in the methanogen reactor (R2), and the methane production rate in the methanogen reactor (R2). The simulation results for VFA formation (dCVFA1/dt) and VFA degradation (dcVFA2/dt) exhibited a tendency to overestimate when operated at low HRT and underestimate at short HRT compared to the experimental results. The steady state of the simulation results exhibited a faster rate of progression than the experimental outcomes. The fitting data for Ksx1 and Ksx2 predominantly comprise dynamically evolving values that exert an influence upon um1 and um1, as well as kd1 and kd2, when the reactor is operated in continuous mode. Furthermore, the factors of inhibitor compounds and microorganism adaptation were not observed across all HRT values in this investigation.